Environmental and genetic determinants of two vitamin D metabolites in healthy Australian children - Bima, A; Pezic, A; Sun, C; Cameron, F; Rodda, C; van der Mei, I; Chiaroni-Clarke, R; Dwyer, T; Kemp, A; Qu, J; Carlin, J; Ellis, J; et al. (De Gruyter, 2017)
Background: Vitamin D deficiency has been associated with adverse health outcomes. We examined genetic and environmental determinants of serum 25(OH)D3 and 1,25(OH)2D3 in childhood. Methods: The study sample consisted of 322 healthy Australian children (predominantly Caucasians) who provided a venous blood sample. A parental interview was conducted and skin phototype and anthropometry measures were assessed. Concentrations of 25(OH)D3 and 1,25(OH)2D3 were measured by selective solid-phase extraction-capillary liquid chromatography-tandem mass spectrometry. These concentrations were deseasonalised where relevant to remove the effect of month of sampling. Results: Deseasonalised log 25(OH)D3 and 1,25(OH)2D3 concentrations were only moderately correlated (r=0.42, p<0.001). The following predicted both 25(OH)D3 and 1,25(OH)2D3: UVR 6 weeks before the interview, natural skin and eye colour, height and vitamin D allelic metabolism score. The following predicted 25(OH)D3 only: lifetime sunburns and vitamin D allelic synthesis score. Overall, 43.5% and 25.6% of variation in 25(OH)D3 and 1,25(OH)2D3 could be explained. After accounting for 25(OH)D3 concentrations, higher UVR 6 weeks before the interview and vitamin D allelic metabolism score further predicted 1,25(OH)2D3 concentrations. Conclusions: Environmental factors and genetic factors contributed to both vitamin D metabolite concentrations. The intriguing finding that the higher ambient UVR contributed to higher 1,25(OH)2D3 after accounting for 25(OH)D3 concentrations requires further evaluation.